Uso das rubricas na autoavaliação e na avaliação por pares: contribuições e desafios - Padilha, Rodrigo Tomaz (2021)
This paper aims to analyze, based on recent international articles, the advantages of the use of rubrics in self and peer assessments, as well as indicate relevant aspects that subsidize formative processes for teachers who work in Middle and High School. The applied methodology was the qualitative narrative research, grounded on international articles published between January 2010 and November 2020, with the intentions of analyzing the recent productions in the field. The results indicate that the use of rubrics in self and peer assessments provides teachers and students with numerous benefits. Among those we may highlight the development of autonomy, self-regulation in learning, improvement of teacher-student and peer communications promoting a more efficient feedback and consequent improvement in performance, stimulating higher quality productions. The analysis also shows the importance of teacher knowledge and preparation to utilize this instrument, demonstrating the relevance of the theme in teacher training. Although advantages can be observed, the study demonstrates some limitation to the use of rubrics such as lack of teacher and student familiarity with the instrument and the necessity of time and dedication for preparation and classroom application